Evaluation of a Commercially Available Canine C‐Reactive Protein Assay Across Institutions and After 2 Years of Frozen Storage - Marion Cambrelin; Amanda F. Bettag; Lorraine E. Prevost; A Russell Moore (Veterinary Clinical Pathology, 2026)
ABSTRACT Background C‐reactive protein (CRP) is a biomarker of systemic inflammation in dogs. There is limited data on inter‐laboratory comparability of the results or the effects of long‐term storage. Objectives (1) Compare CRP measurements across three institutions utilizing the same assay. (2) Evaluate 2‐year stability of CRP in canine serum stored at −80°C. Methods Canine serum was collected and pooled to obtain 100 samples, which were distributed among three veterinary clinical pathology laboratories and evaluated using the same commercially available canine CRP assay. Method comparison was performed according to current recommendations. A subset of samples was then stored at −80°C for 2 years and re‐analyzed to assess long‐term stability. Results Passing‐Bablok and Bland–Altman analyses revealed statistically significant constant and proportional bias between the three laboratories. However, the clinical impact was minimal (mean difference percentages were 4.0%–15.6% and mean difference absolute values were 0.9–4.0 mg/L), differences rarely exceeded the total allowable error (30%), and only two samples crossed the 10 mg/L inflammation decision limit. Similarly, re‐testing after storage revealed a statistically significant increase in CRP concentration (mean difference of 0.75 mg/L, p < 0.001). However, only one sample exhibited a change greater than 30%, and the mean percentage change across all samples was 9.0%. Long‐term storage did not cause any samples to cross the clinical inflammation decision limit. Conclusions While there was statistical evidence of differences between laboratories and after long‐term storage, it was unlikely to alter clinical interpretation or patient management.